Rcs Phosphorelay Responses to Truncated Lipopolysaccharide-Induced Cell Envelope Stress in Yersinia enterocolitica - Jiao Meng; Junhong Xu; Can Huang; Jingyu Chen (Molecules, 2020)
Lipopolysaccharide (LPS) is the major component of the outer membrane of Gram-negative bacteria, and its integrity is monitored by various stress response systems. Although the Rcs system is involved in the envelope stress response and regulates genes controlling numerous bacterial cell functions of Yersinia enterocolitica, whether it can sense the truncated LPS in Y. enterocolitica remains unclear. In this study, the deletion of the Y. enterocolitica waaF gene truncated the structure of LPS and produced a deep rough LPS. The truncated LPS increased the cell surface hydrophobicity and outer membrane permeability, generating cell envelope stress. The truncated LPS also directly exposed the smooth outer membrane to the external environment and attenuated the resistance to adverse conditions, such as impaired survival under polymyxin B and sodium dodecyl sulfate (SDS) exposure. Further phenotypic experiment and gene expression analysis indicated that the truncated LPS was correlated with the activation of the Rcs phosphorelay, thereby repressing cell motility and biofilm formation. Our findings highlight the importance of LPS integrity in maintaining membrane function and broaden the understanding of Rcs phosphorelay signaling in response to cell envelope stress, thus opening new avenues to develop effective antimicrobial agents for combating Y. enterocolitica infections.